OsNAC2 Is Involved in Multiple Hormonal Pathways to Mediate Germination of Rice Seeds and Establishment of Seedling - Yu, Jiangtao; Mao, Chanjuan; Zhong, Qun; Yao, Xuefeng; Li, Peng; Liu, Chunming; Ming, Feng (Frontiers in Plant Science, 2021)
Seed germination and seedling establishment are the preconditions of plant growth, and are antagonistically regulated by the multiple phytohormones, e.g. ethylene, abscisic acid (ABA) and gibberellic acid (GA). However, the interactions between these phytohormones and their upstream transcriptional regulation during seed and seedling growth in rice remains poorly understood. Here, we demonstrate a rice NAC transcription factor, OsNAC2, overexpression of which increases ethylene sensitivity in rice roots during seedling period. Further study showed that OsNAC2 directly activates expression of OsACO and OsACO3, enhancing ethylene synthes is, and then retards seedling establishment. Moreover, OsNAC2 delayed seed germination and coleoptile growth through ABA pathway instead of ethylene and GA pathway, by targeting the promoters of OsNCED3, OsZEP1 and OsABA8ox1. We also found that OsNAC2 regulates downstream targets in a time-dependent manner, binding to the promoter of OsKO2 in seedling period, but not in germination stage. Our finding enriched the regulatory network of ethylene, ABA and GA in rice seed germination and seedling growth, and uncover a new insights into the difference of transcription factors in targeting their downstream components.